KREATIVA PRIMARY SCHOOL MANAGEMENT (QUALITATIVE DESCRIPTIVE ANALYSIS STUDIES) - Harijanto, Sutji; Laihad, Griet Helena; Sugianto, Chafid (UNIVERSITAS PAKUAN, 2021)
One of the primary schools located in Bogor City, West Java which has the concept of improving the students competence accompanied by Islamic religious education, character, environment and provide learning opportunities for children with special needs to learn together with regular students is Kreativa Primary School. This journal is factually written based on the data obtained from the source. from the research results directly to the object location. This study aims to obtain a fact-based picture in the form of data and information on the management of the 5 pillars of the Kreativa Elementary School: Islamic, Green, Leadership, Children Friendly, and Inclusive in order to develop Islamic morals for students. This research uses qualitative methods, with the researcher as an instrument. The data collection techniques used were interviews, observation, and documentation study. Based on existing data and information, it can be concluded that the management function of planning, organizing, directing, and controlling plays an important role in achieving school goals. School management strives to achieve the goal of developing Islamic morals for students through the application of 5 pillars: Islamic, Green, Leadership, Children Friendly, and Inclusive as the basis for educational programs at Kreativa Elementary School. To achieve these goals requires planning that has a strong concept to achieve goals, organizing that is tailored to the needs of the school, directing resources according to the program that has been planned and organized, and control that includes all components of the educational program.